KLASIFIKASI SENJATA API MELALUI SUARA MENGGUNAKAN TRANSFORMASI WAVELET - Fadlisyah Fadlisyah; Syahrial Syahrial (TECHSI - Jurnal Teknik Informatika, 2014)
Classification of guns through sound using Wavelet Transform is a branch of sound processing can be used to identify several types of gunfire. This study uses wavelet transformation for the recognition and classification of firearms training through the noise using Wavelet Transform. The system was then tested by simulating it on the training data and test data to generate the percentage of recognition and classification of the sound of gunfire. Experiments done with several changes in parameter values to obtain the best percentage of recognition and classification. The results of this study in the form of gunfire were classified in accordance with the known brand guns from the calculation of energy using Wavelet Transformation.